Effects of Justicia acuminatissima, or Amazonian Sara Tudo, on ischemic acute kidney injury: an experimental study - Cordeiro, Priscilla Mendes; Fernandes, Sheila Marques; Fonseca, Cassiane Dezoti da; Watanabe, Mirian; Lopes, Sérgio Martins; Vattimo, Maria de Fatima Fernandes (Revista da Escola de Enfermagem da USP, 2019)
Objective To evaluate the effects of Justicia acuminatissima , or Amazonian Sara Tudo , on renal hemodynamics, oxidative profile, and renal histology in rats with ischemic acute kidney injury. Method Preclinical assay with adult male Wistar rats, weighing from 250 g to 350 g, distributed into Sham, ischemia, and ischemia + Sara Tudo groups. Hemodynamic parameters, renal function, oxidative stress, and renal histology were evaluated. Results Pretreatment with Sara Tudo reduced the functional injury, which was shown by the increase in creatinine clearance and thiols; reduction of oxidative markers, renal vascular resistance, and tubulointerstitial injury in the renal tissue; and the significant improvement in renal blood flow. Conclusion The renoprotection provided by Justicia acuminatissima , or Sara Tudo , in cases of ischemic acute kidney injury was characterized by a marked improvement in renal function, reducing the oxidative injury, and impacting on renal histology positively.